An advanced healthcare android application with machine learning - Ridwan, Naeeb MD; Omi, Fuad Tanvir; Ahamed, Protiva (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.